Enhancing the vitality of the National Institutes of Health : organizational change to meet new challenges (Online access: NCBI NCBI Bookshelf., 2003)
The report says that important organizational changes are needed at the National Institutes of Health to ensure the agency meets future challenges effectively. In particular, the report advises NIH to devote additional resources to innovative interdisciplinary research that reflects its strategic objectives and cuts across all agency's institutes and centers. The report recommends that Congress should establish a formal process for determining how specific proposals for changes in the number of NIH agencies and centers should be addressed.